Empowerment Assistance of Cultural Village Community in Jember Distric - Mushthofa Kamal; Bagus P. Yudhia Kurniawan; Retno Sari Mahanani; Taufik Hidayat; Khafidurrohman Agustianto; Ely Mulyadi; Milawaty; Andarula Galushasti (Universitas Muhammadiyah Jember, 2025)
This community service activity aims to increase the capacity of indigenous village communities in Jember Regency in managing tourism potential through the Business Model Canvas (BMC) approach, developing tourism packages, and strengthening tourism awareness movements. The main problems faced by indigenous village communities are suboptimal management of culture-based tourism potential, a lack of tourism product innovation, and weak digital marketing capabilities. This activity was implemented through a participatory approach involving traditional leaders, tourism actors, village officials, and youth groups. The results of the mentoring showed an increase in community knowledge about tourism business models, the creation of local culture-based tourism packages, and increased awareness of the importance of tourism services and environmental preservation. Thus, this activity contributes to strengthening the community economy and preserving local wisdom values ​​in Jember Regency